Marxist philosophy and economic thought in Rosa Luxemburg - Riyadh Ibrahim, Atheer; Al-Khalidi, Mohammed Abdullah (Al-Adab Journal, 2021)
Rosa Luxemburg represented the German left-wing movement, and became one of the most prominent Marxist figures of the revolutionary workers’ movement that worked to organize the party and work to confront the problems hindering the revolutionary movement of the proletariat, as well as it was able to make a significant contribution to the formulation and development of the concepts of Marxism in freedom and revolution and social change Freeing humanity from the raging capitalist monster. Rosa Luxemburg’s lifetime was not at all similar to any of her contemporary women hard time epoch, she fought for renewing ideas and fought for liberation and shared goals and visions with the world in order to apply justice and establish the supreme principles of society as a whole, by fiercely fighting imperialism and capitalism, as she carried attitudes and ideas that transcend Being a woman who rejects reality in the eyes of some, and a fierce struggle that cannot compromise for the sake of her case in the eyes of others, but rather extracts respect from her opponents in a way that makes her perpetuation an imperative in contemporary political thought in general, and Marxist philosophical thought in particular. And cosmic political thought as a whole.